Adherence to iron-folic acid supplementation and its associated factors among pregnant women in Kenya: A multilevel data analysis of the 2022 Kenyan Demographic and Health Survey - Gebrie Getu Alemu; Dagnew Getnet Adugna; Amare Mesfin; Muluken Chanie Agimas; Lemlem Daniel Baffa; Habtamu Wagnew Abuhay; Mekuriaw Nibret Aweke; Tewodros Getaneh Alemu; Nebebe Demis Baykemagn (PLoS ONE, 2025)
Background Iron and folic acid deficiency is a global public health issue, particularly in low- and middle-income countries. Adherence to iron-folic acid supplementation (IFAS) remains low in Kenya. Despite several studies on IFAS adherence in Kenya, they do not assess the national scope and clustering effects using advanced analytical models. Therefore, we aimed to assess IFAS adherence and its associated factors among pregnant women in Kenya using data from the 2022 Kenyan Demographic and Health Survey. Methods A secondary data analysis was conducted using data from the 2022 Kenya Demographic and Health Survey, which was obtained from the official Demographic and Health Survey program database. Weighted samples of 8,460 participants were used in the analysis. The study employed a multivariable multilevel mixed-effects logistic regression model. Variables from the bi-variable model that had p < 0.25 were considered in the multivariable analysis. Variables with a p-value < 0.05 were considered statistically significant in the multivariable model, and the adjusted Odds Ratio (aOR) with its 95% CI was reported. Results The prevalence of IFAS among pregnant women in Kenya was 61.72% (95% CI: 60.68, 62.75). Women aged 20–39 years were 1.3 to 1.7 times more likely to adhere to IFAS during pregnancy, with the likelihood increasing steadily by age group. Moreover, primigravida [aOR = 1.22 (95% CI: 1.06, 1.41)], with a family size of ≥ 10 [aOR = 0.72 (95% CI 0.59, 0.90)], antenatal care visits ≥ 4 [aOR = 3.96 (95% CI: 1.91, 8.23)], first start of antenatal care at the third trimester of pregnancy [aOR = 0.30 (95% CI: 0.15, 0.62)], and with a higher level of education [aOR = 1.6 (95% CI: 1.35, 1.90)] were statistically significant factors associated with adherence to IFAS. Conclusion and recommendation Nearly two in five pregnant women didn’t receive IFAS for the recommended periods. Factors such as maternal age, parity, antenatal visits, and education enhanced IFAS adherence, whereas large family size and starting antenatal care in the third trimester of pregnancy reduced adherence. Therefore, the community, government, and non-governmental organizations should enhance adherence by implementing customized interventions on the factors identified as positive and negative associations.